No closure of the linea alba cervicalis reduces complications in endoscopic thyroidectomy - Tiantian Jiang; Yuanhao Su; Yongke Wu; Cheng Li; Tingkai Sun; Yunhao Li; Yuanyuan Ji; Zhidong Wang (Scientific Reports)
Abstract The benefits of not suturing the linea alba cervicalis and using negative pressure wound therapy after endoscopic thyroidectomy have attracted increasing attention. Therefore, this study aims to determine whether the non-closure of the linea alba cervicalis after endoscopic thyroidectomy can significantly reduce postoperative complications and evaluate the application of NPWT to prevent cavity-related complications. A retrospective analysis was performed. 142 patients were enrolled and divided into two groups, including 71 individuals in the improvement group (no suture of the linea alba cervicalis) and 71 in the conventional group (suture the linea alba cervicalis). Then, the general clinical data and operative indicators were analyzed and compared between the two groups using SPSS 26.0 software. Statistical significance was recognized with P < 0.05. The improvement group showed a lower incidence of neck edema (3/71,4.2% vs. 10/71,14.1%) and a lower score on the Visual Analogue Scale (VAS) 5 days after the operation (3 ± 1.2 vs. 4 ± 1.3) between the two groups (P < 0.05), and there is no significant difference in the overall incidence of postoperative complications between the two groups (P>0.05). No closure of the linea alba cervicalis is safe and feasible after endoscopic thyroidectomy via chest-breast approach, with significantly less incidence of neck edema and lower neck discomfort. In addition, NPWT, providing a novel tool to reduce the occurrence of cavity-related complications in current clinical practice, can be used in whether or not to suture the linea alba cervicalis, which is safe and effective.